Guidelines for Reducing the Return of Credit Analysis Work from the Credit Analysis Center to Branch Offices of the Government Housing Bank - Yoosuk, Salinee; Nakornsathien, Kittipong (RPU Journal of Business Administration, 2025)
This research aimed to: 1) investigate the causes that contribute to the return of credit analysis tasks; and 2) propose effective solutions to reduce the return of credit analysis tasks from the Credit Analysis Center to branch offices of the Government Housing Bank. The study employed both quantitative and qualitative research methods. For the quantitative part, data were collected using questionnaires distributed to 100 credit officers from the Eastern Regional Branch Division of the Government Housing Bank. The statistical tools used for data analysis included frequency, percentage, mean, and standard deviation. For the qualitative part, in-depth interviews were conducted with five credit officers from the same division using the Why-Why Analysis technique. The findings revealed that: 1) the causes of credit task returns from the Credit Analysis Center to the branches stemmed from factors related to personnel, documentation, processes, and tools and equipment; and 2) the proposed solutions include organizing credit analysis training for branch officers at least twice a year to enhance their knowledge and skills, creating clear operational manuals and guidelines for credit analysis, and implementing a system for monitoring and evaluating performance to increase operational efficiency at both the branches and the Credit Analysis Center of the Government Housing Bank.